A comparative study of clinical profile, severity and outcome of acute coronary syndrome in women and men admitted to a tertiary hospital - Tummala, Yugandhar; Hanifah, Mohamed; Ganesh, B. Amirtha (International Journal of Advances in Medicine, 2019)
Background: Coronary artery disease (CAD) has emerged as a major health burden in developing countries. Many recent reports concluded that women with CAD have a worse prognosis than men and also with regards to invasive interventions when compared to men. In this study, author determined the comparative outcomes of ACS in women when compared with men. Methods: This study was conducted in a tertiary care hospital from November 2016 to March 2018. History taking, ECG, cardiac enzymes, 2D-Echo and angiogram were done to diagnose ACS and the appropriate treatment was given. The severity was assessed and compared the outcomes along with complications. Results: The total of 112 patients were treated for ACS, in which, 55 were females and the remaining 57 were males. Majority of the patients in both genders was between the ages of 51-60. In males, STEMI noted 50.8%, NSTEMI in 36.8%, UA in 12.2%. In females, STEMI is noted in 62%, unstable angina in 32.7%, NSTEMI in 27.2%. Six patients (11%) had mortality in the women group and one (1.8%) had died among men. Conclusions: Atypical presentation of ACS was more common in females. Women with ACS had higher complications and higher mortality than men.